EDUKASI DAN PENDAMPINGAN IBU HAMIL KEK PADA KELOMPOK IBU HAMIL DI DESA AWANG BANGKAL BARAT - Suhrawardi, Suhrawardi; Januarsih, Januarsih; Isrowiyatun Daiyah (Bajang Institute, 2024)
If a pregnant woman experiences anemia and SEVERITY, she will be at risk during her pregnancy, childbirth and the baby that will be born. During pregnancy, pregnant women who experience anemia and SEVERITY are at risk of abortion, impaired growth of fetal brain cells, the distribution of nutrients from mother to fetus will also be severely disrupted, so that it will make the baby born potentially experience Low Birth Weight Babies (LBW) which if the condition is not handled will continue to stunting, fetal growth abnormalities and others. During childbirth, pregnant women who experience anemia and SEZ are at risk of bleeding during childbirth and in the last ten years, bleeding has always coexisted with Preeclampsia in the top two contributors to the Maternal Mortality Rate in Indonesia. Stunting in toddlers is influenced by maternal nutritional history such as chronic energy deficiency (CED) and iron nutritional anemia (AGB). The nutritional status of the mother before and during pregnancy can affect fetal growth. If the mother's nutritional status is normal before and during pregnancy, it is likely that she will give birth to a healthy, full-term baby with normal weight. Poor fetal growth of pregnant women with SEZ will result in low birth weight (LBW) babies. A pregnant woman will give birth to a healthy baby if her health and nutrition levels are in good condition